Block periodization of high-intensity aerobic intervals provides superior training effects in trained cyclists - Rønnestad, B. R.; Hansen, J.; Ellefsen, S. (Scandinavian Journal of Medicine & Science in Sports, 2014)
The purpose of this study was to compare the effect of two different methods of organizing endurance training in trained cyclists. One group of cyclists performed block periodization, wherein the first week constituted five sessions of high-intensity aerobic training (HIT), followed by 3 weeks of one weekly HIT session and focus on low-intensity training (LIT) (BP; n = 10, VO2max = 62 ± 2 mL/kg/min). Another group of cyclists performed a more traditional organization, with 4 weeks of two weekly HIT sessions interspersed with LIT (TRAD; n = 9, VO2max = 63 ± 2 mL/kg/min). Similar volumes of both HIT and LIT was performed in the two groups. While BP increased VO2max, peak power output (Wmax) and power output at 2 mmol/L [la-] by 4.6 ± 3.7%, 2.1 ± 2.8%, and 10 ± 12%, respectively (P < 0.05), no changes occurred in TRAD. BP showed relative improvements in VO2max compared with TRAD (P < 0.05). Mean effect size (ES) of the relative improvement in VO2max, Wmax, and power output at 2 mmol/L [la-] revealed large to moderate effects of BP training compared with TRAD training (ES = 1.34, ES = 0.85, and ES = 0.71, respectively). The present study suggests that block periodization of training provides superior adaptations to traditional organization during a 4-week endurance training period, despite similar training volume and intensity.